Learning activity development through Key Explored Method (KEM) for the instructor in Faculty of Education, Souphanouvong University, Academic year 2018-2020 - KHOTSAIGNOH, Saiphone; SOULIVONG, Phetsamone; PHETSOMBATH, Sengdao; SYVANKHAM , Sengdeuan; LIAMAHER, YearHer (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
This research intended to conduct an experiment through the use of Key Explored method (KEM) in the instruction of History of international labor movement, which a step of the development of new learning method in Faculty of Education, Souphanouvong University; The research aimed to develop the effectiveness of new teaching technique via KEM with the set creteria 80/80, to find out the efficiency index (E.I) of the learning archievment and evaluate the student`s perspectives who participated in this. The sampling students focused on final year students who have been majoring in political science 58 students, the instrument of this research consists of KEM teaching plan, there was an objective test with multiple choicewith difficulty level ranged between 0.40-0.86; a discrimination level (rxy) between 0.29-0.96; and the questionnaire for assessing the student`s perpective with 5 difference rating scale in respond to 75 items with IOC = 1; the reliability was of .964 The research findings found that: The effectiveness of applying KEM teacing plan in the instruction was (E1/E2) 78.22/78.78; which lower than the set creteria of 80/80 The effective index (E.I) of the student`s learning via KEM for History of international labor movement equaled 0.68243 and it showed that the student`s progress was 68.24% Overall, the attitude of the student about KEM activities was overall at the high lavel In conclusion, it was found that the use of KEM activities in the instruction of History of international labor movement for political students was efficient as expected and highly accepted by the students, it was very beneficial to teaching-learning, leading to the development of an effective teaching handbooks or manual in the future